Characterisation and outcomes of ARDS secondary to pneumonia in patients with and without SARS-CoV-2: a single-centre experience. Issue 1 (30th November 2020) - Mahida, Rahul Y; Chotalia, Minesh; Alderman, Joseph; Patel, Chhaya; Hayden, Amber; Desai, Ruchi; Beesley, Emily; Crowley, Louise E; Soltan, Marina; Bangash, Mansoor; Parekh, Dhruv; Patel, Jaimin; et al.
Abstract : Introduction: Acute respiratory distress syndrome (ARDS) is the major cause of mortality in patients with SARS-CoV-2 pneumonia. It appears that development of 'cytokine storm' in patients with SARS-CoV-2 pneumonia precipitates progression to ARDS. However, severity scores on admission do not predict severity or mortality in patients with SARS-CoV-2 pneumonia. Our objective was to determine whether patients with SARS-CoV-2 ARDS are clinically distinct, therefore requiring alternative management strategies, compared with other patients with ARDS. We report a single-centre retrospective study comparing the characteristics and outcomes of patients with ARDS with and without SARS-CoV-2. Methods: Two intensive care unit (ICU) cohorts of patients at the Queen Elizabeth Hospital Birmingham were analysed: SARS-CoV-2 patients admitted between 11 March and 21 April 2020 and all patients with community-acquired pneumonia (CAP) from bacterial or viral infection who developed ARDS between 1 January 2017 and 1 November 2019. All data were routinely collected on the hospital's electronic patient records. Results: A greater proportion of SARS-CoV-2 patients were from an Asian ethnic group (p=0.002). SARS-CoV-2 patients had lower circulating leucocytes, neutrophils and monocytes (p<0.0001), but higher CRP (p=0.016) on ICU admission. SARS-CoV-2 patients required a longer duration of mechanical ventilation (p=0.01), but had lower vasopressor requirements (p=0.016). Discussion: The clinical syndromes and respiratory mechanics of SARS-CoV-2 and CAP-ARDS are broadly similar. However, SARS-CoV-2 patients initially have a lower requirement for vasopressor support, fewer circulating leukocytes and require prolonged ventilation support. Further studies are required to determine whether the dysregulated inflammation observed in SARS-CoV-2 ARDS may contribute to the increased duration of respiratory failure.